KINETICS AND EQUILIBRIUM MODEL OF Pb(II) AND Cd(II) ADSORPTION ONTO TETRAKIS-THIOMETHYL-C-4-METHOXYPHENYLCALIX[4]RESORCINARENE - Suryadi Budi Utomo; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa (Indonesian Journal of Chemistry, 2012)
The ability of tetrakis-thiomethyl-C-4-methoxyphenylcalix[4]resorcinarene for trapping Pb(II) and Cd(II) from aqueous solution at different pH, contact times, and initial metal concentration was investigated. Concentration of metal ions before and after interaction was analyzed by Atomic Absorption Spectrophotometer (AAS). The result indicated that tetrakis-thiomethyl-C-4-methoxyphenylcalix[4]resorcinarene is a good host for metal ions, where Cd(II) sorption capacity was higher than that of Pb(II). Effect of pH on batch experiments for the mentioned ions indicated that the optimum pH for metal binding were 5 for both of lead(II) and cadmium(II). In order to investigate the mechanism of adsorption, the 1st-order, pseudo 1st-order, and pseudo 2nd-order kinetic models were used. The adsorption model of metal ions on the resorcinarene followed pseudo second order of Ho & McKay expression. The equilibrium adsorption isotherm has been analyzed by Langmuir and Freundlich equations. Langmuir model had the higher correlation coefficient than that of Freundlich model.